Aksi Bersih Sampah di Pantai Wisata Tanjung Bemban dalam Rangka World Clean Up Day Kota Batam 2024 - GITA PRAJATI; Handi Wilujeng Nugroho; Yosef Adicita; Kurniawan Hamidi; Roselyn Indah Kurniati; Lina Hanarisanty; Zefri Azharman (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2025)
World Cleanup Day gives positive impact to environmental care activities in Indonesia. Environmental Services of Batam participated into World Cleanup Day action by sorting waste from public residence in 2021. In the year of 2024, Batam still involved in World Cleanup Day action. One of the location was Tanjung Bemban, Nongsa. The purpose of this social service is to partipate in world clean up day by cleaning up the waste in Tanjung Bemban beach. The method is application of participatory approach. There are two steps in this action. The first step is introduction and preparation that conducted by committee of World Cleanup Day. Whereas, the second step is clean up the waste in the specified locations. The waste classified into four categories. Participants collected and weighted the waste to the committee. Beach Cleanup Day 2024 in Tanjung Bemban can collected waste around 235.3 kilograms, consist of 97.3 kilograms organic waste, 88.4 kilograms plastic waste and 49.6 kilograms other type of waste. This action also involved many participants from various parties, such as government, military, NGOs, universities and schools. Beach clean up action expected to increase practice in waste management.